Creating early childhood Islamic spiritual education with cartoons Rara and Nussa as a method for Quranic learning - Kamilah, Nurul; Sutrisno, Sutrisno (Universitas Islam Malang, 2025)
The aims of this study is to determine the content of the Qur'an in the film Nusa and Rara. The education of the Qur'an holds significant importance for children. Individuals can attain knowledge of God through the Qur'an. The Nussa and Rara animation represents an effective digital medium. Facilitating children's comprehension of the Qur'an and incorporating Islamic values into their everyday practices. Because Merdeka curriculum and Profil Pelajar Pancasila are used in schools, so that learning the Qur'an can be integrated into children's daily lives. This study employs descriptive qualitative methodologies. The data source is the animated film